7p+12=13+6p

Simple and best practice solution for 7p+12=13+6p equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7p+12=13+6p equation:


Simplifying
7p + 12 = 13 + 6p

Reorder the terms:
12 + 7p = 13 + 6p

Solving
12 + 7p = 13 + 6p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-6p' to each side of the equation.
12 + 7p + -6p = 13 + 6p + -6p

Combine like terms: 7p + -6p = 1p
12 + 1p = 13 + 6p + -6p

Combine like terms: 6p + -6p = 0
12 + 1p = 13 + 0
12 + 1p = 13

Add '-12' to each side of the equation.
12 + -12 + 1p = 13 + -12

Combine like terms: 12 + -12 = 0
0 + 1p = 13 + -12
1p = 13 + -12

Combine like terms: 13 + -12 = 1
1p = 1

Divide each side by '1'.
p = 1

Simplifying
p = 1

See similar equations:

| 12-4x-x^2=36-16x^2+16 | | 2+10= | | -5.2x-3.3=22.7 | | 10y+2=7 | | 2*d=5d | | 4[-2(4x+3)+2(5x-5)]= | | 9y+(-3y-5)=4y-7 | | 2m(4m)= | | 2m(11n)= | | 2m(11n+3)= | | 0.4x+5.2=4.6 | | 9(2x-4)=3(6x+1) | | x^2-11x-7=0 | | 4t+3=2t+11 | | 4-9x=-11x | | 3-(x-1)=x+2 | | 12-3x=8x+2 | | 4+8x+25-5y=23 | | 103-7x=11x+23 | | 5-(x-7)=x-4 | | 7-7x=57-21x | | X^3-6x^2+8x-2=0 | | 11x+3=2(5x-1)+5 | | 0=2x-16 | | 0.4x+4.4=3.8 | | 0=-x+15 | | o=-x+15 | | 10-2(2-x)=18 | | x+4+3+x-2+x^2+2x+3x-4=30 | | (x+7)(x+9)=2x+62 | | 20x^3-6x=0 | | (x+2)*x=80 |

Equations solver categories